2013
DOI: 10.3389/fneur.2013.00031
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Diagnosis and Localization of Lateralized Temporal Lobe Epilepsy Using Interictal FDG-PET

Abstract: Interictal FDG-PET (iPET) is a core tool for localizing the epileptogenic focus, potentially before structural MRI, that does not require rare and transient epileptiform discharges or seizures on EEG. The visual interpretation of iPET is challenging and requires years of epilepsy-specific expertise. We have developed an automated computer-aided diagnostic (CAD) tool that has the potential to work both independent of and synergistically with expert analysis. Our tool operates on distributed metabolic changes ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 104 publications
(142 reference statements)
0
48
1
Order By: Relevance
“…The ample evidences of advanced research using multimodal combinational non-invasive neuroimaging techniques like MRI, MRS, f-MRI, FDG-PET, SPECT, and MEG have revealed that most of the cases of TLE patients are accompanied by pathological changes in brain structure and function network, including cortical and subcortical (hippocampus and parahippocampus) structures [12][13][14]. Such multimodal combinational imaging (structural and functional) approaches are being suggested to detect the laterization of TLE with ictal and interictal onset in pre-surgical diagnostic purpose [15][16][17][18][19][20]. Regardless, epilepsy occasionally is a clinical problem as regards medical management and the problem becomes acute in developing countries as there is often delay in clinical diagnosis due to the limited resources, large patient load, and health care manpower constraints [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The ample evidences of advanced research using multimodal combinational non-invasive neuroimaging techniques like MRI, MRS, f-MRI, FDG-PET, SPECT, and MEG have revealed that most of the cases of TLE patients are accompanied by pathological changes in brain structure and function network, including cortical and subcortical (hippocampus and parahippocampus) structures [12][13][14]. Such multimodal combinational imaging (structural and functional) approaches are being suggested to detect the laterization of TLE with ictal and interictal onset in pre-surgical diagnostic purpose [15][16][17][18][19][20]. Regardless, epilepsy occasionally is a clinical problem as regards medical management and the problem becomes acute in developing countries as there is often delay in clinical diagnosis due to the limited resources, large patient load, and health care manpower constraints [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as we only utilized T1 MRI data and did not incorporate signal variation from T2/FLAIR scans (Coan et al, 2014, Cantor-Rivera et al, 2015 or alterations found in PET (Kerr et al, 2013) or DTI data (Cantor-Rivera et al, 2015), it is clear that there is still much room for improving classifier performance. Thus, in the future, an even more comprehensive model that identifies subgroups, incorporates other imaging modalities in addition to clinical and neuropsychological data, would likely be superior in regards to both diagnosis and predicting treatment outcomes, thus achieving clinical utility.…”
Section: Discussionmentioning
confidence: 99%
“…These include tumor imaging (1), neurologic diseases such as epilepsy (2) and Alzheimer disease (3)(4)(5), and psychiatric disorders such as major depression (6). Hence, PET using the radiolabeled glucose analog 18 F-FDG offers an excellent opportunity for imaging and quantification of glucose metabolism.…”
mentioning
confidence: 99%